The Psychological, Physiological, and Behavioral Responses of Patients to Magnetic Resonance Imaging (MRI): A Systematic Review and Meta-Analysis - Madl, Janika; Nieto Alvarez, Isabel; Amft, Oliver; Rohleder, Nicolas; Becker, Linda (Journal of Magnetic Resonance Imaging, 2023)
Background: MRI is generally well-tolerated although it may induce physiological stress responses and anxiety in patients. Purpose: Investigate the psychological, physiological, and behavioral responses of patients to MRI, their evolution over time, and influencing factors. Study Type: Systematic review with meta-analysis. Population: 181,371 adult patients from 44 studies undergoing clinical MRI. Assessment: Pubmed, PsycInfo, Web of Science, and Scopus were systematically searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Quality appraisal was conducted with the Joanna Briggs Institute critical appraisal tools. Meta-analysis was conducted via Meta-Essentials workbooks when five studies were available for an outcome. Psychological and behavioral outcomes could be analyzed. Psychological outcomes were anxiety (State–Trait-Anxiety Inventory, STAI-S; 37) and willingness to undergo MRI again. Behavioral outcomes included unexpected behaviors: No shows, sedation, failed scans, and motion artifacts. Year of publication, sex, age, and positioning were examined as moderators. Statistical Tests: Meta-analysis, Hedge's g. A P value <0.05 was considered to indicate statistical significance. Results: Of 12,755 initial studies, 104 studies were included in methodological review and 44 (181,371 patients) in meta-analysis. Anxiety did not significantly reduce from pre- to post-MRI (Hedge's g = −0.20, P = 0.051). Pooled values of STAI-S (37) were 44.93 (pre-MRI) and 40.36 (post-MRI). Of all patients, 3.9% reported unwillingness to undergo MRI again. Pooled prevalence of unexpected patient behavior was 11.4%; rates for singular behaviors were: Failed scans, 2.1%; no-shows, 11.5%; sedation, 3.3%; motion artifacts, 12.2%. Year of publication was not a significant moderator (all P > 0.169); that is, the patients' response was not improved in recent vs. older studies. Meta-analysis of physiological responses was not feasible since preconditions were not met for any outcome. Data Conclusion: Advancements of MRI technology alone may not be sufficient to eliminate anxiety in patients undergoing MRI and related unexpected behaviors. Level of Evidence: 1. Technical Efficacy: Stage 5.
CRIS-Team Scopus Importer:2023-12-01
Keywords: anxiety; artifacts; magnetic resonance imaging; patient outcome assessment; prevalence; stress